The Impact of Management and Organizational Culture on Creativity in the Hotel Industry - Olimpia State; Maria-Cristina Iorgulescu (Amfiteatru Economic Journal, 2014)
In today's business environment, characterized by instability and unpredictability, organizations' success depends on their ability to adapt and manage the changes required. Therefore, in order to achieve long-term corporate success, companies need to have a culture that encourages creativity and innovation. The aim of the article is to investigate the link between corporate culture and creativity and the impact of the management form on organizational culture. The research highlights the Romanian hotel industry culture, using Hofstede's model. Considering their impact on innovation, there were taken into consideration three factors: individualism, power distance and long term orientation. The article investigates how these factors are influenced by the hotel's exploitation form and their impact on organizational creativity. The research was conducted on two hotels in Bucharest, affiliated to an international hotel chain. In order to identify the impact of the exploitation form on the hotel's organizational culture, one of the accommodation units is operated under a management contract, while the other operates under a franchise agreement. The study is based on a survey conducted among the employees of the two hotels. Results indicate differences regarding the corporate culture between the hotel operated under a management contract and the unit operated under a franchise agreement. Recommendations on how to foster employees' creativity are suggested. The implications of the findings are discussed, considering the limitations and future research directions.
Keywords: D23; L83; M14; 330; creativity; innovation; organizational culture; management; Hofstede's model